Upaya Pemanfaatan Dana UMKM Untuk Peningkatan Kesejahteraan Masyarakat Di Kecamatan Medan Baru - Nisa Hutasoit; Gusti Pirandy (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Poverty is a serious social problem in developing countries including Indonesia. The problem of poverty is a complex and multidimensional problem related to society, culture, economy and other aspects. Micro, small and medium enterprises (MSMEs) are an alternative that people can choose to increase their income. MSMEs, especially MSEs, play a very important role in creating jobs and sources of income for the people of Indonesia, proving to be more able to survive the economic crisis that hit Indonesia in 1998. The worst point with a huge negative impact in almost every sector. This study is expected to explain the use of MSME funds by entrepreneurs and their impact on improving people's welfare. This study aims to determine and clarify the efficiency of the use of community MSME funds in Medan Baru District, North Sumatra.